2012
DOI: 10.5005/jp-journals-10022-1013
|View full text |Cite
|
Sign up to set email alerts
|

Management of Gingival Pigmentation with Diode Laser: Is It a Predictive Tool?

Abstract: Today, an attractive smile is the vogue for many individuals. Gingival health and appearance are essential components for an attractive smile and removal of unsightly pigmented gingival is the need for a pleasant and confident smile. In some populations, gingival pigmentation seems to be a genetic trait and is irrespective of age and gender, hence gingival pigmentation is termed as physiologic or racial gingival pigmentation. Intraoral pigmentation is seen due to the presence of the fundamental pigment melanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 101 publications
0
11
0
Order By: Relevance
“…In some studies, DOPI and Hedin indices were used for evaluation of clinical changes of pigmentation 28) and in other studies, clinicians expressed their opinion about changes of pigmentation of qualitative and descriptive method by commenting on clinical observation 3,24,[27][28][29] or viewing of photographs 17,24,28,29) . They didn't use special indices; therefore, we were not able to do exact comparative evaluation with their study.…”
Section: Intensity (Dopi) and Extension (Hedin Melanin Index) Changesmentioning
confidence: 99%
“…In some studies, DOPI and Hedin indices were used for evaluation of clinical changes of pigmentation 28) and in other studies, clinicians expressed their opinion about changes of pigmentation of qualitative and descriptive method by commenting on clinical observation 3,24,[27][28][29] or viewing of photographs 17,24,28,29) . They didn't use special indices; therefore, we were not able to do exact comparative evaluation with their study.…”
Section: Intensity (Dopi) and Extension (Hedin Melanin Index) Changesmentioning
confidence: 99%
“…Atsawasuwan et al 35 reported no recurrence during 11-to 13-month follow-up period in four patients using Nd:YAG laser for depigmentation. Doshi et al 36 reported in a case reportusing diode laser for depigmentationthat there were mild melanotic patches that started to occur after 3 months of treatment in different gingival regions. Those patches increased in size for a year after treatment.…”
Section: Diodementioning
confidence: 99%
“…Different treatment modalities have been utilized as a part to overcome the gingival hyperpigmentation. The selection of the appropriate depigmenting technique ought to be based on the type of presenting pigment, gingival biotype, clinical experience, patient's financial status and individual preferences [18,19] (Doshi et al, 2012 andPatil et al, 2015).…”
Section: Introductionmentioning
confidence: 99%